Le Parallélisme: esthétique du solipsisme dans le cinéma de Michael Mann - Kalla, Stéphane (Verbum – Analecta Neolatina, 2014)
The paper presents certain key features from a philosophical and phenomenological point of view of the aesthetics of Michael Mann, a leading film maker of modernity. We try to identify the aesthetic, phenomenological and metaphysical issues of a unique formalism, parallelism.